Occupational Therapy in hospital settings: an assistive solution for the prevention and treatment of Pressure Injuries (Research, Society and Development, 2020)
This article prioritizes the report of an intervention plan developed by occupational therapists in Hospital Contexts, translated into an assistive solution according to the needs of adult patients hospitalized in the Wards, pointing out the possibilities that the assistive product offers, for the prevention and the treatment of Pressure Injuries (LPP). This study is based on the theoretical-methodological framework of Ergology, which aims to understand human work, originating from studies called Pluridisciplinary Analysis of Work Situations. It was developed in a Federal Hospital Unit in Rio de Janeiro, which is a promising element, as it includes several health teams, with a commitment to developing safe practices and quality health care. The object of study is divided into an Action Plan incorporating assistive products with guidelines on how to use them and a Care Plan with the actions / guidelines of care for patients and family members aiming at postural adequacy with the placement of assistive products of bed positioning, used in the clinical practice of the occupational therapist. It will be urgent to carry out future studies in order to monitor and obtain a return on the preventive care carried out; deepen issues related to the practical application of the use of assistive products and embark on studies that include the informal caregivers of patients in this process.